The African Continental Free Trade Agreement : Welfare Gains Estimates from a General Equilibrium Model - Abrego, Lisandro (IMF Working Papers; Working Paper ;, 2019)
In March 2018, representatives of member countries of the African Union signed the African Continental Free Trade Area (AfCFTA) agreement. This agreement provides a framework for trade liberalization in goods and services and is expected to eventually cover all African countries. Using a multi-country, multi-sector general equilibrium model based on Costinot and Rodriguez-Clare (2014), we estimate the welfare effects of the AfCFTA for 45 countries in Africa. Three different model specifications-comprising both perfect competition and monopolistic competition-are used. Simulations include full elimination of import tariffs and partial but substantial reduction in non-tariff barriers (NTBs). Results reveal significant potential welfare gains from trade liberalization in Africa. As intra-regional import tariffs in the continent are already low, the bulk of these gains come from lowering NTBs. Overall gains for the continent are broadly similar under the three model specifications used, with considerable variation of potential welfare gains across countries in all model structures.